Right diaphragmatic hernia: a case report - Ingar-Pinedo, Jaime (2014)
We present case which shows the different approach that should have congenital diaphragmatic hernia (CDH) right relative to the left side, in terms of prenatal assessment to establish prognosis for survival, as most used parameters established left congenital diaphragmatic herna. It also shows the increased difficulty in diagnosing the right CDH.